H2 PRODUCTION BY PULSE ELECTROLYSIS - Fatih Andiwijaya, Ahmad
Fossil fuels based energy systems have a negative impact such as global warming and the depletion of natural resources. Hydrogen based energy system is the best solution for reducing dependence on fossil fuels. Hydrogen can be produced from water by electrolysis. The main obstacle of the electrolysis process is the high electrical energy needs, so it takes concentrated electrolyte solution and the use of expensive platinum electrode to reduce energy. Pulse electrolysis is an alternative of electrolysis process that utilize high frequency electrical signal to split water molecules into hydrogen gas and H2O2 as byproduct using stainless steel electrodes. Pulse electrolysis experiments were carried out using three variables, i.e. electric power, frequency, and concentration of KOH electrolyte. The hydrogen gas concentration is determined by GC analysis and calculations, whereas H2O2 is determined indirectly through SEM, SEM/EDX and AAS analysis as well as calculations based on GC analysis result. Process performance is evaluated on the basis of hydrogen gas yield, hydrogen production energy efficiency and H2O2/O2 selectivity. In this research, H2 gas and H2O2 can be obtained simultaneously by pulse electrolysis process using AISI 316 stainless steel electrode and KOH concentration 0,5 M with theoretical energy efficiency 75,5% and selectivity 7,75 ?mol H2O2/?mol O2 at standard conditions. H2 production volume increases with increasing electric power and electrolyte concentration within range of KOH 0,1-0,5 M, while frequency variations are not directly correlated to H2 production.